Tooth brushing for oral prophylaxis - Haruaki Hayasaki, DDS, PhD; Issei Saitoh, DDS, PhD; Kuniko Nakakura-Ohshima, DDS, PhD; Mika Hanasaki, DDS; Yukiko Nogami, DH; Tsutomu Nakajima, DDS; Emi Inada, DDS, PhD; Tomonori Iwasaki, DDS, PhD; Yoko Iwase, DDS, PhD; Tadashi Sawami, DDS, PhD; Katsushige Kawasaki, DDS, PhD; Nozomi Murakami, DDS; et al. (Elsevier, 2014)
Control of plaque and debris is essential for the prevention of inflammatory periodontal diseases and dental caries, because plaque is the primary etiological factor in the introduction and development of both of these infection-oriented diseases. Plaque removal with a toothbrush is the most frequently used method of oral hygiene. Powered toothbrushes were developed beginning in the 1960s and are now widely used in developed countries. The bristles of a toothbrush should be able to reach and clean efficiently most areas of the mouth, and recently the design of both manual and powered toothbrushes has focused on the ability to reach and clean interproximal tooth surfaces. An individual's tooth brushing behavior, including force, duration, motivation and motion, are also critical to tooth brushing efficacy. Dental floss and the type of toothpaste play additional important roles as auxiliary tools for oral prophylaxis. Dental professionals should help their care-receivers' meet the requirements of oral hygiene to maintain their QOL. This article reviews these topics.